2010
DOI: 10.1677/erc-10-0073
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of relaxin receptor RXFP1 decreases prostate cancer growth and metastasis

Abstract: Relaxin (RLN) is a small peptide hormone expressed in several cancers of reproductive and endocrine organs. Increased expression of RLN in prostate cancer correlates with aggressive cancer. RLN G-protein-coupled receptor (RLN family peptide receptor 1, RXFP1) is expressed in both androgen receptor (AR)-positive and -negative prostate cancers as well as in prostate cancer cell lines. RLN behaves as a cell growth factor and increases invasiveness and proliferation of cancer cells in vitro and in vivo. The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 45 publications
3
74
0
Order By: Relevance
“…An elevated ANGPTL4 in CRCs is also correlated with shorter disease-free survival rates (25). Furthermore, the (11,35,36). In contrast, studies have also shown that increased ANGPTL4 expression inhibits melanoma, lung, and colorectal tumor growth, metastasis, and angiogenesis (10,37).…”
Section: Angptl4 Expression and Its Transcriptional Regulation In Hummentioning
confidence: 97%
“…An elevated ANGPTL4 in CRCs is also correlated with shorter disease-free survival rates (25). Furthermore, the (11,35,36). In contrast, studies have also shown that increased ANGPTL4 expression inhibits melanoma, lung, and colorectal tumor growth, metastasis, and angiogenesis (10,37).…”
Section: Angptl4 Expression and Its Transcriptional Regulation In Hummentioning
confidence: 97%
“…Specific RXFP1 and negative control siRNA were supplied by Qiagen (Valencia, CA). The siRNA sequence used for RXFP1 gene silencing (siRXFP1) was GGAUGUCAAGUGCUCCCUUtt (sense strand) (13,17). Negative control siRNA (siNC) with no significant sequence similarity to human gene sequences was used as control.…”
Section: Matrigel Invasion Assay Bd Biocoat Matrigel Invasionmentioning
confidence: 99%
“…Negative control siRNA (siNC) with no significant sequence similarity to human gene sequences was used as control. The PC3 cells were transfected with siRXFP1 and siNC (5 µg each) using Nucleofector device as previously described (17). Transfected cells were harvested after 72 h, the protein was extracted from the total cell lysate for Western blot experiments.…”
Section: Matrigel Invasion Assay Bd Biocoat Matrigel Invasionmentioning
confidence: 99%
See 2 more Smart Citations